Rancang Aplikasi Monitoring Ibadah Siswa Berbasis Web di SMA Negeri 1 V Koto Kampuang Dalam - Amelia, Dita; Supriadi, Supriadi; Musril, Hari Antoni; Efriyanti, Liza (Indonesian Research Journal on Education, 2023)
This research is based on several problems, namely in the process of monitoring worship in schools, teachers monitor students once a week which is inefficient. Another problem is the worship and student monitoring reports can be lost because they are only summarized on paper. Not infrequently students are less honest when filling out their worship records because worship reports are not made routinely by the teacher. This is what motivates the author to design a web-based daily worship monitoring application.For students this application is designed with the hope of helping and making it easier for teachers and students to monitor the daily worship that has taken place. The research method used by the author is a research and development method. This method is a research method used to develop or validate products for use in education and learning. The research model used is the ADDIE model which is the Waterfall version of the development model, namely design, develop, implement, evaluate and SDLC. Monitoring of student worship, which is one of the activities in schools designed to monitor the performance of students' daily worship. This application is designed by the author using the PHP MySQLprogramming language. In this study, the authors conducted a trial for the product, namely using the effectiveness test, practicality test and effectiveness test. The research conducted by the author resulted in a web-based student worship monitoring application at SMA Negeri 1 V Koto Kampung Dalam. This app is available for students and teachers. From the product validity test the results are proven valid, the validity test is carried out by 3 experts who have expertise in the fields of computing and education. In addition, the teacher's practicality test resulted in a very practical score. Students are then tested foreffectiveness only to get Effective results.